EXPLORING THE UNTAPPED POTENTIALS OF ISLAMIC SOCIAL FUNDS IN ISLAMIC HOME FINANCING FOR LOW INCOME FAMILY (International Journal of Islamic Business, 2017)
Islamic home financing in Islamic financial institution hitherto remains an arduous to resolve as it contains many issues. One of the main issues is interest benchmarking that inseparable part of banking system. Amid this reality, many Islamic financial institutions ignored the existence of Islamic social funds to mobilize the funds and hence ameliorate the affordability of low income family to purchase a house. This paper therefore aims to explore the untapped potentials of Islamic social funds such as waqf, Shodaqah and infaq to mobilize funds and create more affordable house for low income families. This paper undertakes library review as qualitative approach to strengthen the discussion. This paper concludes that the synergy between Nazir of social funds and Islamic micro finance institution able to produce Islamic social funds to be utilized to help low income family afford to purchase a house. This paper implies practically on the expected remarkable growth of Islamic micro finance institution offering Islamic home financing using Islamic social funds approach.